1998
DOI: 10.1177/153857449803200205
|View full text |Cite
|
Sign up to set email alerts
|

The Durability of Duplex-Directed Manual Occlusion of Femoral False Aneurysms

Abstract: Duplex-directed manual occlusion (DDMO) has emerged as a first line treatment in selected cases of iatrogenic pseudoaneurysms related to interventional and therapeutic femoral artery cannulations. Early recurrences after successful closure of femoral false aneurysms (FFA) are described in the literature; however, very little long-term follow-up data are available. Therefore, the authors reviewed their experience with DDMO of 45 FFAs between February 1991 and December 1994. Follow-up was arranged to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It must be mentioned that most studies found a lower success rate in patients treated with anticoagulants. 1, 13 We did not treat a normal Brescia-Cimino fistula of the forearm but an autogenous fistula of the upper arm. It is possible that such a fistula tolerates a greater compression without risk of a thrombosis.…”
mentioning
confidence: 99%
“…It must be mentioned that most studies found a lower success rate in patients treated with anticoagulants. 1, 13 We did not treat a normal Brescia-Cimino fistula of the forearm but an autogenous fistula of the upper arm. It is possible that such a fistula tolerates a greater compression without risk of a thrombosis.…”
mentioning
confidence: 99%